Implementation of ISO quality management system in construction companies of Malaysia - Tan, Chin Keng; Syazwan , Zainul Kamal (Penerbit UTHM, 2016)
ISO 9001 Quality Management System is one of the ISO 9000 set of standards that provides a series of guidelines on how to establish a quality system to manage the processes that affect its product or services. There are many benefits offered by ISO but it does not mean if a company managed to secure the certification, they will be able to experience all the beneficial outcomes. Construction companies that wish to implement the system should be prepared for the upcoming obstacles that may be encountered during the process. The objectives of this research are to identify the benefits of implementing ISO 9001 Quality Management System in the Malaysian construction companies, to identify the problems faced by construction companies in implementing ISO 9001 Quality Management System and to identify the strategies adopted by the ISO certified construction companies in overcoming or minimizing the implementation problems. Case study approach has been selected to collect data for this research. For the purpose of the case study, five construction companies were selected to be interviewed. One representative form each company is interviewed in order to get more information from their perspective regarding the benefits, problems and strategies for the implementation of ISO 9001 QMS. The research findings concluded that improved company’s management & work efficiency as the most important benefit from the implementation of the system while lack of awareness on the system among staff is the most significant problem. It is suggested training and audit (internal and external) need to be enhanced to overcome those implementation problems.